Location of sites that inhibit progression of replication forks in the terminus region of Escherichia coli. - Pelletier, A J (1988)
We used a Southern hybridization assay to locate precisely the sites at which DNA replication is arrested in the terminus region of the Escherichia coli chromosome. The assay was based on the properties of restriction fragments that contain stalled replication forks. Replication forks that entered the terminus from the clockwise direction with respect to the genetic map were inhibited near manA at a site called T2, which we located at kilobase 442 on the physical map of Bouché (J. P. Bouché, J. Mol. Biol. 154:1-20, 1982). Those that entered the terminus region traveling in the counterclockwise direction were inhibited near pyrF at a site called T1, which we located at kilobase 90. In each case we found only a single, precise site of arrest. Inhibition at T1 was not detectable in our assay in strains lacking the trans-acting locus tus, which is located near T2 and is required for T1 to function. We demonstrated that the sites of inhibition are also used during termination of replication in exponentially growing, wild-type cells. In all previous studies on the terminus of E. coli, inhibition has only been detected in strains that were modified so that the origin used was placed near the terminus to force the use of the sites of inhibition.